Radiation induced cardiovascular disease: An odyssey of bedside-bench-bedside approach. (November 2020) - Rikhi, Rishi; Samra, Gursharan; Arustamyan, Michael; Patel, Jay; Zhou, Leon; Bungo, Brandon; Moudgil, Rohit
Abstract: The journey to Mars will be an ambitious, yet arduous task as it will entail culmination of all the information we have gathered over many decades. While the mission is of utmost importance, preservation of astronaut's well-being is paramount also. To that end, mitigation of radiation risk especially afflicting cardiovascular disease (CVD) is of great interest and challenge. Current data from astronauts on low earth orbit and Apollo missions provides insight on the risk of CVD from radiation exposure. However, data is limited given the small cohort size of astronauts who embarked on just nine prolonged missions. Therefore, a cerebral approach to understanding and mitigating risks are essential. This paper discusses the need for a predictive preclinical model to help understand and mitigate the effects of radiation on astronauts. We will discuss strengths and limitations of preclinical models and the methods of validating and constructing a model to predict human clinical outcomes. Our bedside-bench-bedside approach focuses on adapting the preclinical model through common investigative tools used between humans and animals. The result will be an optimization of preclinical model to a point of being a surrogate clinical model capable of predicting CVD outcomes in astronauts exposed to radiation.